Environmental factors and seasonal effect on the potential harmful algae presence at Ambon Bay, Indonesia - Mohammad Mahmudi; Evellin Dewi Lusiana; Endang Y. Herawati; Lukas G. Serihollo (Society for Indonesian Biodiversity, 2020)
Abstract. Mahmudi M, Lusiana ED, Herawati EY, Serihollo LG. 2020. Environmental factors and seasonal effects on the potential harmful algae presence at Ambon Bay, Indonesia. Biodiversitas 21: 3101-3107. Marine and coastal areas are susceptive to harmful algae presence which can lead to Harmful Algae Blooms (HABs). Major drivers for this event are climate change, domestic and industrial activities. These alter the environmental condition in marine ecosystems which caused the shift of phytoplankton community. This study aims to analyze the environmental factors affecting the harmful algae occurrence in Ambon Bay as well as the seasonal change during west monsoon and first transition in regards to this issue. There were six environmental variables accounted in this research which measured in situ and ex-situ. The results showed that there were three algae divisions that formed the phytoplankton structure in Ambon Bay, namely Bacillariophyceae, Dinophyceae, and Cyanophyceae. These divisions have been reported as the cause of previous HABs in the area. Furthermore, algae density during first transition season was higher than during west monsoon season, but the composition of phytoplankton community was stable in which dominated by harmful algae such as Chaetoceros, Skeletonema, Nitzschia, Ceratium, Pyrodinium, Dinophysis, Alexandrium, and Trichodesmium. Meanwhile, based on Canonical Correspondence Analysis (CCA), temperature and nutrients were the main factors that highly associated with the presence and abundance of harmful.